Retinal energy state in rats with experimental diabetes and axial myopia - Михейцева, І.М.; Амаієд, Ахмед; Коломійчук, Сергій (Oftalmologicheskiĭ zhurnal., 2023)
Background: Elucidating the pathogenesis of diabetic retinopathy (DR) for further development of methods of treatment and prevention of the disease is an important medical and social task for ophthalmologists. The development of DR in the presence of myopia has some special features. In the presence of myopia, the diabetic complications in the retina are less severe than in emmetropia. The mechanisms of this paradoxical impact of eye myopization on the severity of these complications are, however, still unknown. Purpose: To examine the state of retinal energy metabolism based on evaluation of biochemical markers of mitochondrial function (lactate, pyruvate, adenosine triphosphate (ATP) and adenosine diphosphate (ADP) levels and succinate dehydrogenase activity) in rats with streptozotocin (STZ)-induced diabetes that developed in the presence of axial myopia, compared to rats with diabetes alone and those with myopia alone. Material and Methods: High axial myopia was produced in two-week animals by surgically fusing the eyelids of both eyes and maintaining these animals under conditions of reduced illumination for two weeks. A 15 mg/kg intraperitoneal streptozotocin injection for 5 days was used for inducing diabetes mellitus in rats with induced axial myopia and intact rats. Animals in the control group were maintained under conditions of natural illumination. In two months, all rats were euthanized under anesthesia, and their eyes were enucleated. ATP, ADP, lactate, and pyruvate levels were measured in blood and retinal specimens and ATP/ADP ratio and lactate/pyruvate ratio were determined. Succinate dehydrogenase activity was determined in isolated retinal mitochondria. For statistical analysis of biochemical results, Student’s t-test was conducted (Statistica software). Results: Rats with diabetes alone exhibited lower retinal and plasma energy metabolism characteristics (ATP, ADP, and succinate dehydrogenase activity), and developed retinal hypoxia, with retinal lactate and pyruvate levels being 1.838-fold and 1.455-fold higher, respectively, and their ratio, 26.5% higher, compared to controls. In animals with STZ-induced diabetes in the presence of axial hypoxia, retinal lactate and pyruvate levels were 20.2% and 15.5% lower, respectively, and their ratio was lower (36.5 versus 38.7), compared to rats with diabetes alone, indicating lower hypoxia in the setting of eye myopization. In addition, in rats with diabetes in the presence of axial hypoxia, plasma and retinal ATP levels were 21.8% and 21.2% higher, respectively, and retinal succinate dehydrogenase activity, 20.8% higher, compared to rats with diabetes alone. Conclusion: In experimental diabetes, an increase in the axial length of the eye (i.e., eye myopization) is accompanied by activation of energy processes and the development of hypoxia adaptation in retinal cells.